Nuclear Weapons Before the International Court of Justice: A Critique of the Marshall Islands v United Kingdom Decision - Awmee, Devesh (Victoria University of Wellington Law Review, 2018)
The International Court of Justice recently gave judgment in Obligations Concerning Negotiations Relating to Cessation of the Nuclear Arms Race and to Nuclear Disarmament. The case concerned three parallel claims brought by the Marshall Islands against India, Pakistan and the United Kingdom for their alleged failure to fulfil obligations concerning negotiations relating to the cessation of the nuclear arms race and nuclear disarmament under art VI of the Non-Proliferation Treaty and customary international law. The Court in all three proceedings dismissed the claims at the preliminary objections phase on the sole ground that a legal dispute did not exist between the parties. In determining whether a legal dispute existed, the Court appears to have deviated from the objective determination taken in its previous jurisprudence by introducing, for the first time, a new requirement of "awareness". The Court also failed to address the other preliminary objections brought by the United Kingdom such as the Monetary Gold principle, which appears to have been a more credible avenue for the Court to dismiss the case. The case illustrates the failure by the Court to yet again confront the issue of nuclear weapons.